Computer-aided detection of colorectal polyps using a newly generated deep convolutional neural network: from development to first clinical experience - Pfeifer, Lukas; Neufert, Clemens; Leppkes, Moritz; Waldner, Maximilian; Hafner, Michael; Beyer, Albert; Hoffman, Arthur; Siersema, Peter D.; Neurath, Markus; Rath, Timo (European Journal of Gastroenterology & Hepatology, 2021)
Aim The use of artificial intelligence represents an objective approach to increase endoscopist's adenoma detection rate (ADR) and limit interoperator variability. In this study, we evaluated a newly developed deep convolutional neural network (DCNN) for automated detection of colorectal polyps ex vivo as well as in a first in-human trial.
CRIS-Team WoS Importer:2022-03-18